Türk sigorta sektörüne yapılan yabancı sermayeli yatırımların sebepleri ve sektöre etkileri - Turaboğlu, Turgut Tuğrul (My University, 2008)
Foreign Insurance Companies, The Potantial of Insurance Market, ABSTRACT THE REASONS AND EFFECTS OF FOREIGN CAPITAL INVESTMENT IN TURKISH INSURANCE SECTOR There has been a significant amount of movement in Turkish insurance sector that has been behind the average global rate for many years. With the help of legal regulations, the goverment has changed its policies about insurance sector. There has been an increase in the interest of foreign-capital supported companies which leads to new alliances and cooperations. In this study, the information about the historical development of global and Turkish insurance is given. In addition to that, more information is also given about the role of Turkish insurance sector in financial system, the activating factors that lead foreigncapital supported companies to invest and the effect of these foreign investment inter of socio-economic.
Keywords: Bankalar ve Bankacılık; Sigortacılık; Yabancı Sermaye; Yatırım Yönetimi